2018
DOI: 10.1097/ico.0000000000001767
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Microbial Keratitis and Nasolacrimal Duct Obstruction: Concordance, Etiopathogenesis, and Outcome

Abstract: Purpose: Nasolacrimal duct obstruction (NLDO) is believed to be a risk factor for microbial keratitis (MK). The primary objective of this study was to look at microbiological concordance between corneal scraping and lacrimal sac flora in patients with concurrent MK and NLDO. The secondary objective was to compare microbiological isolates from MK and NLDO, MK alone, NLDO alone, and healthy subjects. Methods: A prospective comparative study of 146 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Although NLDO has been suggested as a major risk factor for non-healing bacterial keratitis (BK) [47], until recently few studies have confirmed an association between NLDO and BK [48,49]. Recent work from India adds weight to this by demonstrating that patients with untreated NLDO and MK have a worse clinical outcome [50]. For this reason, at our institution all patients with MK undergo lacrimal syringing.…”
Section: Discussionmentioning
confidence: 99%
“…Although NLDO has been suggested as a major risk factor for non-healing bacterial keratitis (BK) [47], until recently few studies have confirmed an association between NLDO and BK [48,49]. Recent work from India adds weight to this by demonstrating that patients with untreated NLDO and MK have a worse clinical outcome [50]. For this reason, at our institution all patients with MK undergo lacrimal syringing.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few studies regarding the spectrum of bacteria of chronic dacryocystitis, suggesting coagulase-negative Staphylococcus (CoNS) and Staphylococcus aureus, the most frequently isolated organisms in lacrimal sac infections. [6][7][8][9] The purpose of this study was to analyze the microbial spectrum of infectious keratitis in patients with co-existing nasolacrimal duct obstruction (NLDO). The pattern of antibiotic susceptibility of bacterial isolates was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous report showed that coagulase-negative Staphylococci are the most common isolates from the nasolacrimal sac by conventional culture methods. 8 Other studies reported that in healthy subjects the microbiome in the nasolacrimal sac is usually dominated by Staphylococci and Corynebacterium . In contrast, a significantly lower relative abundance of Corynebacterium was observed in a case of NLDO.…”
Section: Discussionmentioning
confidence: 98%